Kinetics of the non-isothermal desorption of ethanol absorbed onto CMS-3A - Jovančić, Nikola S.; Adnađević, Borivoj K.; Jovanović, Jelena D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The kinetics of the desorption of ethanol previously absorbed onto carbon molecular sieves (CMS-3A) was studied using the non-isothermal thermogravimetric technique. The dependence of activation energy (Ea,α) for a particular degree of desorption (α) was established. It was confirmed that the non-isothermal desorption of ethanol was a kinetically complex process. A novel mathematical model for the kinetics of non-isothermal desorption for the absorbed ethanol is established. This model is based on the proposed dependence of the specific desorption rate on time/temperature. The correlation dependences of the model parameters β and η on heating rates were established. A general kinetic equation for the non-isothermal desorption of ethanol was developed. It was found that the specific desorption rate at every single heating rate increases, whereas Ea, decreases during the desorption process.